(untitled) (Research, Society and Development, 2022)
With the Covid-19 pandemic, teaching was remote and needed to innovate daily for classes to be attractive to students. This article presents an investigation, of a didactic intervention with the support of Augmented Reality (AR), the understanding of the cells of the human body during a science class for elementary school students. The case study was developed with 53 students in the ninth grade of elementary science. Students were asked to use cards with AR and interact with their families explaining the content on the cells, using the same technology. The results showed that AR is an important tool to support science classes in the content of cells in the human body, making visible what would remain in the imagination and enabling interaction with cellular structures, facilitating learning. AR technology helped students learn and contributed to the activity being interesting and fun, motivating students in the learning process.